FORESTRY IN AVESTO - Kimsanbaeva Shakhnoza; Abduraimova Muqaddas (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, trees and forests have long been valued and respected in Central Asia. Therefore, in our country, special attention is paid to digging canals, plowing and cultivating the land, planting trees, planting trees and shrubs, the development of forestry. Our ancestors deeply understood and respected that trees and forests are a priceless blessing for man and society. The Avesto, a historical monument of our ancestors, pays great attention to the preservation of Mother Nature as the apple of one's eye, the preservation of the purity of the environment, the preservation and reproduction of forests, the most useful source of wealth for man.